KEPUASAN DAN LOYALITAS KONSUMEN PADA ONLINE MARKET DI INDONESIA - F. Alia Humairah; glory glory (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2009)
The goal of this research activity is to investigate things that will improve consumer • satifaction and loyalty of online stores in Indonesia. Researchers can take advantage of the result obtained and then inform it to companies so they know what things need to be improved to maintain their customers. The findings in this study indicate that there is a positive influence of a) adaptation (adaptation), (b) interaction (interactivity), (c) maintenance (nurturing), (d) commitment (commitment), (e) network (network), (f) diversity (assortment), (g) the ease of transaction (transaction ease), and (h) the agreement of usaage (engagement) towards customer satisfaction, there is a positive influence customer satisfaction to customer loyalty, there is a positive influence of Inertia towards the relationship between customer satisfaction and customer loyalty, and there is a positive influence od Trust towards the relationship between customer satisfaction to customer loyalty. The result of this research has implications for the business online which are to increase customers satisfaction and loyalty and to scholars who want to develop the theory. Further research are expected to use global online shopping as a comparison and adding the other variables that also affect customer satisfaction and loyalty in the online market.keyword: Customer Satisfaction, Loyalty, and Online Market